PENERAPAN PERSAMAAN GEOTERMOMETER (SiO2)p DI LAPANGAN PANAS BUMI SULI, AMBON - Handayani, Helda (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2012)
Suli hot springs area has a low level of acidity or neutral pH ranges (7,2–7,7). It is also supported by a high chloride concentration value, which ranges (208,87-226,27) ppm. Thisshows that the area on station 1, 2, 3, and 4 are located in areas with water flow into the upper reservoir (upflow) and belongs to hot water domination reservoir tipe (water heatedreservoir). Reservoir temperature is calculated by the formula geotermometer (SiO2)p considered whether applied in the four kinds geotermometer equation because it gives the calculation results are not much different temperature and has a value of rms-error is less than 2%. Reservoir temperature at a hot springs station Suli possible temperature (161 ± 0,9)oC. Reservoir temperature at station 2 hot spring Suli possible hot water temperature (172 ± 1,0)oC. Reservoir temperature at station 3 hot springs Suli possible temperature (171 ±0,9)oC. Reservoir temperature at station 4 hot springs Suli possible temperature (169 ± 1,0)oC.